Lateral meniscal injury without medial meniscal injury indicates the existence of the Segond fracture in ACL-deficient knees - Nobutada Suzuki; Atsuya Watanabe; Taishi Ninomiya; Hirofumi Nakajima; Manato Horii; Shotaro Watanabe; Yuki Shiko; Takahisa Sasho (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2024)
Background/Objective: The purpose of this study was to find factors indicating the occurrence of the Segond fracture, a specific type of anterolateral ligament injury. Methods: From January 2015 to December 2017, we retrospectively reviewed the medical records of patients diagnosed with acute anterior cruciate ligament (ACL) injury who underwent reconstruction within 90 days of injury. Diagnosis of the Segond fracture was determined either by magnetic resonance imaging or plain radiographs. Factors examined were: age at surgery, sex, body mass index (kg/m2), status of menisci, and activities led to ACL injury. After univariate screening, multivariate logistic regression analyses were performed. Patients were divided into four groups based on the presence of lateral meniscal (LM) and/or medial meniscal (MM) injuries and compared with respect to the occurrence of Segond fractures. Results: A total of 375 patients were included (163 males, 212 females), with mean age 25.8 years old. Among them, 22 of 375 (5.9 %) had a Segond fracture. We identified injured lateral menisci (adjusted odds ratio (aOR), 3.029; 95 % Confidence Interval (CI), 1.206–7.609; P = 0.018), intact medial menisci (aOR, 0.229; 95 % CI, 0.065–0.810; P = 0.022), and higher body mass index (aOR, 1.102; 95 % CI, 1.008–1.205; P = 0.034) as factors indicative of the occurrence of Segond fracture. LM injury without MM injury suggested the existence of a Segond fracture. Conclusion: LM injury without a MM injury indicated the occurrence of a Segond fracture. Higher body mass index also increased the risk for Segond fracture occurrence.